Impacts of sugar and trans fat overconsumptions on development of polycystic ovary syndrome and female fertility - Sununta Youngwanichsetha (Global Journal of Fertility and Research - Peertechz Publications, 2020)
Achievement of fertility is the expectation and desire of women in reproductive age. However, many women face sub-infertility or infertility. Overconsumption of foods and drinks containing sugar and trans fat are observed to be associated with female infertility. Sugar is commonly added in many sweetened drinks and desserts. Trans fat is ingredients of bakery and processed foods. Overconsumption of sugar and trans fat leading to obesity, metabolic syndrome and insulin resistance are known to be risk factors for developing of polycystic ovary syndrome (PCOS) and fertility problems among women [1].